Analisis Kinerja Jaringan Internet dengan Metode Class Based Queueing di Universitas Dhyana Pura - Bernadus, I Nyoman; Gunantara, Nyoman; Saputra, Komang Oka (Majalah Ilmiah Teknologi Elektro, 2019)
Dhyana Pura University (Undhira) is one of the higher education institutions that utilize the advancement of information technology to achieve optimal results. The observation shows that bandwidth utilization is not well managed. On this basis, this study aims to analyze Quality of Service (QoS) with parameters throughput, delay, packet loss, jitter and bandwidth by Class Based Queuing (CBQ) methods as a queue method that regulates usage network bandwidth allocated to each user. This study also measured the level of employee satisfaction using the Customer Satisfaction Index (CSI) method. The results of this study indicate that the CBQ method is a method of bandwidth management in reducing bandwidth in crisis clients, so as to increase employee satisfaction in using internet services in the process of service for students.